IMPLEMENTASI METODE DEMONSTRASI TERHADAP PRESTASI BELAJAR FIQIH BAB WUDHU SISWA KELAS VII MTS AL-MA’ARIF MUJUR PRAYA TIMUR - Hairussolihin, Hairussolihin; Idawati, Idawati; Rozali, Muhammad (STKIP Pesisir Selatan, 2025)
The purpose of this study was to determine how to implement the demonstration method in teaching fiqh on wudhu, and to analyze the extent to which the application of this method can help improve the learning achievement of seventh grade students at MTs Al-Ma'arif Mujur Praya Timur. This study used a qualitative approach with data collection techniques through observation, interviews, and documentation. The research informants included the principal, fiqh teachers, and seventh grade students at MTs Al-Ma'arif Mujur Praya Timur. The results showed that the demonstration method was implemented by the teacher demonstrating the procedure for wudhu directly in front of the students, then asking the students to imitate it in turns while being guided and corrected if there were any mistakes. This process enables students to not only understand the theory but also be able to practice wudu correctly. The application of the demonstration method has been proven to help improve student learning achievement, both in cognitive aspects (knowledge of the pillars and requirements of wudu), affective aspects (interest, motivation, and positive attitudes in learning), and psychomotor aspects (skills in practicing wudu in accordance with Islamic law). Therefore, it can be concluded that the demonstration method is an effective learning strategy in improving students' understanding and skills in fiqh learning.